Propuesta de estudio de tiempos y movimientos para la estandarizanción de métodos en el área de producción de la empresa “CASA MUEBLES RIVERA” ubicada en el Valle del Cauca. (2022)
The study of times and movements is a methodology used to know, identify and analyze the processes for activities to generate delays, bottlenecks or downtime that the production process in a company and according to the data obtained, they can be reduced or eliminated to give solution to these shortcomings and thus optimize times and movements in each work area.